HUBUNGAN ANTARA SELF-ESTEEM DENGAN FEAR OF MISSING OUT (FOMO) PADA REMAJA PEREMPUAN PENGGUNA AKTIF MEDIA SOSIAL - Priska Meita Anggraeni; Wahyuni Kristinawati (Journal of Innovation Research and Knowledge, 2025)
This study examines the relationship between self-esteem and Fear of Missing Out (FoMO) in adolescent girls who are active on social media. This study applied quantitative methods with a correlational design, involving 119 female adolescent participants aged 15- 19 years who actively use social media more than 3 hours a day. The measuring instruments in this study used the self-esteem scale and the fear of missing out (FoMO) scale which had been adapted in Indonesian by Syawalli (2023). The Spearman rank correlation coefficient test results (rs) for self-esteem with FoMO amounted to -0.732, with a p value = 0.000 (<0.05). The results of the research analysis indicate a highly significant negative relationship between self-esteem and Fear of Missing Out (FoMO) in adolescent girls who are active on social media. That is, the higher the level of self-esteem, the lower the level of FoMO in adolescent girls who actively use social media, and vice versa, the lower the self- esteem, the higher the FoMO in them.